ORGANISMS CAUSING OSTEOMYELITIS AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN AMONG PATIENTS SEEKING CARE ATA TERTIARY CARE ORTHOPEDIC CENTER - Jhamnani, Rohit; Gupta, Aakansha; Verma, Divya (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to study the organisms causing osteomyelitis and their antimicrobial susceptibility pattern from a tertiary care teaching hospital located in a region of Madhya Pradesh. Methods: Fifty clinically diagnosed cases of osteomyelitis visiting the medical college and seeking care for the same in orthopedics department during the study period formed the study population. Pus samples were collected and sent to microbiology laboratory for culture and testing of their antimicrobial susceptibility as per the standard guidelines. Results: Out of 50 water samples gathered, 25, 14, and 11 samples of water were gathered from municipal tap water, government hand pump, and water cooler separately. Close to half of the examples were viewed as inadmissible. Escherichia coli was viewed as answerable for 26% of tests while Pseudomonas in 1/5th of gathered examples. Staphylococcus aureus, 14 (87.5%) were found resistant to Penicillin-G. Pseudomonas aeruginosa, 14 (100%) were found resistant to ampicillin, whereas more than half cases were found be resistant to antibiotics, namely, ciprofloxacin, ofloxacin, and cephotaxime, respectively. Conclusion: We observed changes in the patterns of isolated organisms and the establishment of higher levels of antibiotic resistance among bacterial isolates in osteomyelitis cases. It is imperative that monitoring be prioritized to track etiological changes and to adhere to a single health policy to stop the multidrug-resistant bacteria threat.